Aliens in disguise - Smith, Clete Barrett (Smith, Clete Barrett. Intergalactic Bed & Breakfast., 2013)
When a pair of UFO-watchers disguised as aliens tries to get inside the Intergalactic Bed & Breakfast to broadcast their findings, it is up to David and Amy to keep the imposters at bay.